2017
DOI: 10.1016/j.cmi.2017.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin versus azithromycin for treating legionella pneumonia: a propensity score analysis

Abstract: In our study, no significant differences in most outcomes were found between patients treated with levofloxacin and those treated with azithromycin. Due to the small number of deaths, results regarding mortality should be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 24 publications
0
21
0
3
Order By: Relevance
“…Conventionally, levofloxacin, which is a fluoroquinolone antibiotic, is bactericidal and has been considered the first-line drug for Legionnaires' disease ( 19 - 21 ). However, the latest research showed that the effects were not markedly different between levofloxacin and intravenous azithromycin, which is a macrolide antibacterial agent ( 22 ). Ciprofloxacin, pazufloxacin, levofloxacin, garenoxacin, moxifloxacin, clarithromycin, azithromycin, and rifampicin were all shown to have relatively good antibacterial activity against Legionella with no resistant strains ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, levofloxacin, which is a fluoroquinolone antibiotic, is bactericidal and has been considered the first-line drug for Legionnaires' disease ( 19 - 21 ). However, the latest research showed that the effects were not markedly different between levofloxacin and intravenous azithromycin, which is a macrolide antibacterial agent ( 22 ). Ciprofloxacin, pazufloxacin, levofloxacin, garenoxacin, moxifloxacin, clarithromycin, azithromycin, and rifampicin were all shown to have relatively good antibacterial activity against Legionella with no resistant strains ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…After a good clinical response is detected, it can be switched to the oral route. In patients with severe disease or unresponsive to monotherapy, the addition of rifampin is recommended [45,50]. The recommended Azithromycin dose is 500 mg IV/PO q24h for 5 days.…”
Section: Treatmentmentioning
confidence: 99%
“…Primary outcome was overall 30-day in-hospital mortality. Thirty-six patients were excluded, 175 patients received levofloxacin, 177 patients received azithromycin and 58 patients received clarithromycin, without statistical significant difference for in-hospital 30-day mortality between the cohorts [24].…”
Section: Targeted Therapymentioning
confidence: 99%